Acute effects of MDMA on trust, cooperative behaviour and empathy: A double-blind, placebo-controlled experiment. (May 2021) - Borissova, Anna; Ferguson, Bart; Wall, Matthew B; Morgan, Celia JA; Carhart-Harris, Robin L; Bolstridge, Mark; Bloomfield, Michael AP; Williams, Tim M; Feilding, Amanda; Murphy, Kevin; Tyacke, Robin J; Erritzoe, David; et al.
Background: 3, 4-Methylenedioxymethamphetamine (MDMA) is being actively researched as an adjunct to psychotherapy. It may be beneficial to trust, empathy and cooperative behaviour due to its acute prosocial effects. Aim: To test (a) the acute effects of MDMA on measures of empathy, trust and cooperative behaviour, and (b) subacute changes in mood three days after MDMA administration. Methods: Twenty-five participants ( n =7 female), participated in this double-blind, repeated-measures, placebo-controlled experiment. Participants attended two acute sessions, one week apart. Each acute session was followed by a subacute session three days later. Participants received placebo (100 mg ascorbic acid) during one acute session, and MDMA (100 mg MDMA-HCl) at the other, with order counterbalanced. Participants completed the following tasks assessing prosocial behaviour: a trust investment task, a trustworthy face rating task, an empathic stories task, a public project game, a dictator game and an ultimatum game. Participants reported subjective effects. Blood was taken pre-drug, 2 and 4 hours post-drug, and tested for plasma MDMA levels. Results: MDMA acutely increased self-reported 'closeness to others' and 'euphoria' and increased plasma concentrations of MDMA. MDMA did not significantly change task-based empathy, trust or cooperative behaviour. Using Bayesian analyses, we found evidence that MDMA and placebo did not differ in their effects on empathy and cooperative behaviour. MDMA did not significantly change subacute mood and this was supported by our Bayesian analyses. Conclusion: Despite augmentation in plasma MDMA levels and subjective drug effects, we found no increase in prosocial behaviour in a laboratory setting.